THE MAN WHO KNEW TOO MUCH: Žižek and the Balkans - Jukić, Tatjana (Array, 2013)
Slavoj Žižek’s view of the Balkans has recently been critiqued as procolonial, in that he casts the Balkans as the unconscious of Europe and therefore deprives it of the cogito, which remains definitive of Europe. This critique, with its Cartesian and Lacanian implications, bears on the very constitution of Žižek’s critical gesture, because it tends to homogenise both psychoanalysis and the philosophy Lacanian psychoanalysis engages with into colonialism. Taking up Žižek’s Marx, particularly the way in which his Marx comes together with the Balkans in The Fragile Absolute, I argue that the Balkans in Žižek traces the metonymic logic of the international which dehomogenises Europe to begin with and displaces the logic of colonialism. What emerges instead is a political imaginary where Žižek’s Lacanian script registers a shift towards configurations formative to the work of Deleuze: the shift mobilised already in Žižek’s engagement with Hitchcock’s cinema where Hitchcock labours as the specimen story of Žižek’s philosophy cum psychoanalysis.